An oil-water separation method for treating oilfield produced liquid by using biochar demulsifier

CN122682300BActive Publication Date: 2026-10-23DAQING NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611181088.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-23
Estimated Expiration
2046-08-05

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种利用生物炭破乳剂处理油田采出液的油水分离方法,其解决了现有的油田采出液乳液稳定、油水分离慢、破乳剂难回收及出水含油量不稳定技术问题

Benefits of technology

本发明通过生物炭破乳剂对油田采出液进行处理,能够提高乳化油滴的破稳效率和油水分层速度。生物炭破乳剂中含有生物炭和磁性镧铈锆铁磷硅纳米颗粒,生物炭具有孔道吸附和表面富集作用,能够吸附油田采出液中的分散油滴、胶质、沥青质和悬浮颗粒;磁性镧铈锆铁磷硅纳米颗粒能够增强生物炭破乳剂与油水界面膜的接触作用,使界面膜强度降低,促使细小油滴相互碰撞、变形和聚并,从而得到更易分层的聚并体系,提高三相体系中油层、水层和含破乳剂固体富集层的分离清晰度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122682300B_ABST
    Figure CN122682300B_ABST
Patent Text Reader

Abstract

The application discloses a kind of oil-water separation methods for treating oilfield produced liquid using biochar demulsifier in the technical field of oilfield produced liquid treatment, the method is first filtered, heated and stirred, then biochar demulsifier is added to form demulsifier dispersion system, after stirring coalescence, standing and bottom additional magnetic field enrichment, oil layer, water layer and solid enrichment layer containing demulsifier are formed, and oil layer, treated water and solid enrichment layer are collected respectively.The biochar demulsifier is prepared by preparing citrate-stabilized ferroferric oxide magnetic nanometer core, silica-coated ferroferric oxide magnetic skeleton, lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated magnetic skeleton and magnetic lanthanum-cerium-zirconium-iron phosphorus-silicon nanoparticles, and then compounded with biochar.The application can weaken the stability of oil-water interface film, promote oil droplet coalescence and magnetic field enrichment, realize rapid separation of oil-water-solid three-phase, and improve the performance of demulsifier recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oilfield produced fluid treatment technology, specifically to an oil-water separation method using biochar demulsifier to treat oilfield produced fluid. Background Technology

[0002] Produced fluids are complex oil-water mixtures generated during oilfield extraction, gathering, transportation, and preliminary processing. They typically contain crude oil, water, inorganic salts, silt, corrosion products, gums, asphaltene, and oil recovery additives. As oilfields enter the mid-to-late stages of production, the water content of the produced fluids increases, oil droplet size decreases, emulsification intensifies, and the oil-water interface film becomes more stable, significantly increasing the difficulty of oil-water separation. Traditional methods such as gravity settling, heated settling, centrifugation, and conventional filtration are effective for handling large-diameter floating oil particles, but for stable emulsified oil, fine dispersed oil droplets, and produced fluid systems containing solid particles, they often suffer from long separation times, large fluctuations in the oil content of the effluent, high equipment loads, and insufficient processing efficiency, making it difficult to meet the requirements for produced fluid reinjection, reuse, or subsequent advanced treatment.

[0003] In current oilfield produced fluid treatment, chemical demulsifiers are commonly used to weaken the oil-water interface film, causing oil droplets to coalesce and achieve oil-water stratification. Common demulsifiers are mostly polyether-based, resin-based, or surfactant-based organic chemicals. While they can increase the demulsification rate to some extent, they still have drawbacks such as high consumption, insufficient adaptability to high-salt, high-viscosity systems, potential secondary pollution from residual chemicals, and difficulties in recycling and reuse. On the other hand, biochar has advantages such as well-developed pore structure, wide availability, low cost, and abundant surface functional groups, making it suitable for adsorbing oil droplets, organic pollutants, and suspended particles. However, ordinary biochar is difficult to recover after dispersion in oilfield produced fluids, and its ability to demulsify stable emulsions solely through pore adsorption is limited, easily leading to unstable treatment efficiency and solid material loss.

[0004] Therefore, developing a biochar demulsifier and its oil-water separation method that combines demulsification, adsorption, aggregation, and recyclability is of great significance. Introducing a magnetic inorganic structure into the biochar system endows the demulsifier with magnetic field responsiveness, enabling it to rapidly enrich under an external magnetic field after treating produced fluid, facilitating oil-water-solid three-phase separation and material regeneration. Simultaneously, the silicon, phosphorus, lanthanum, cerium, zirconium, and iron components on the surface of the magnetic inorganic structure can improve the material's interfacial interaction ability and dispersion stability, which helps weaken the oil-water interfacial film, promote oil droplet collision and aggregation, and enhance the enrichment of suspended solids and asphaltenes. However, existing technologies still lack an oil-water separation method that is relatively simple, allows for demulsifier recyclability, is suitable for oilfield produced fluid treatment, and balances separation efficiency and recyclability. Summary of the Invention

[0005] The purpose of this invention is to provide an oil-water separation method for treating oilfield produced fluids using biochar demulsifiers, which solves the existing technical problems of unstable oilfield produced fluid emulsions, slow oil-water separation, difficulty in recovering demulsifiers, and unstable oil content in the produced water.

[0006] The present invention achieves the above objectives through the following technical solutions: An oil-water separation method using biochar as a demulsifier to treat oilfield produced fluids includes the following steps: S1. By weight, filter 900-1100 parts of oilfield produced fluid and add it to the demulsification reactor. Heat the mixture to 40-60℃ and stir to obtain pretreated oilfield produced fluid. Add 0.5-3.0 parts of biochar demulsifier to the pretreated oilfield produced fluid and continue stirring to obtain a demulsifier dispersion system. S2. Transfer the demulsifier dispersion system to an oil-water separator and stir at 40-60℃ to obtain an agglomeration system; S3. Allow the aggregated system to stand, and apply an external magnetic field to the bottom of the oil-water separator to obtain a three-phase system; S4. Collect the oil layer from the upper part of the three-phase system, discharge the water layer from the middle of the three-phase system and filter it to obtain treated water; collect the solid enrichment layer containing demulsifier from the bottom of the three-phase system, and wash, wash and dry the solid enrichment layer containing demulsifier with anhydrous ethanol.

[0007] In this invention, the mechanism of the oil-water separation method using biochar demulsifier to treat oilfield produced fluid lies in the fact that after filtration, larger solid impurities are removed from the produced fluid. Heating and stirring reduce the viscosity of the oil phase and improve the mass transfer state between dispersed oil droplets and the aqueous phase, making the emulsion system more susceptible to the action of biochar demulsifier. After the biochar demulsifier is added to the pretreated oilfield produced fluid, the porous structure of biochar adsorbs and enriches dispersed oil droplets, colloids, asphaltenes, and fine suspended particles. The silicon, phosphorus, lanthanum, cerium, zirconium, iron, phosphorus, and silicon composite sites on the surface of magnetic lanthanum, cerium, zirconium, and iron nanoparticles adsorb and interact with polar components, oxygen-containing components, and solid particle surfaces in the oil-water interface film, reducing the integrity and mechanical strength of the interface film and making it easier for fine oil droplets to contact, deform, and aggregate. After the demulsifier dispersion system is transferred to the oil-water separator, under warm and stirred conditions, the biochar demulsifier continuously collides with the emulsified oil droplets. Some oil droplets are adsorbed on the surface and near the pores of the biochar demulsifier. Subsequently, the stirring intensity is reduced, and multiple oil droplets gradually aggregate into larger oil droplets or oil droplet aggregates through the bridging effect on the surface of the biochar demulsifier, thus obtaining an aggregated system. After the aggregated system is allowed to stand, the larger oil droplets float to the surface under the action of density difference to form an oil layer, and the continuous aqueous phase gradually clarifies to form a water layer. At the same time, the biochar demulsifier loaded with oil droplets, suspended particles, and interfacial contaminants, due to its magnetic structure of iron oxide, accumulates to the bottom under the action of an external magnetic field at the bottom of the oil-water separator, forming a solid enrichment layer containing the demulsifier. Thus, a three-phase system consisting of an oil layer, a water layer, and a solid enrichment layer containing the demulsifier is obtained. Subsequently, the oil layer is collected from the upper part of the three-phase system, the water layer is discharged from the middle of the three-phase system and filtered to obtain treated water, and the solid enrichment layer containing demulsifier is collected from the bottom of the three-phase system. Anhydrous ethanol has a elution effect on the oil phase components adsorbed in the solid enrichment layer containing demulsifier. After washing and drying, some of the attached oil stains can be removed and the surface contact ability and magnetic response ability of biochar demulsifier can be restored, thereby achieving effective separation of oil, water and biochar demulsifier in oilfield produced fluid.

[0008] According to a preferred embodiment of the present invention, in step S1, the stirring time after heating to 40-60°C is 5-10 minutes.

[0009] According to a preferred embodiment of the present invention, in step S2, the stirring time at 40-60°C is 3-6 minutes.

[0010] According to a preferred embodiment of the present invention, in step S3, the settling time is 20-40 minutes.

[0011] According to a preferred embodiment of the present invention, in step S3, the magnetic field strength of the applied magnetic field is 100-300mT.

[0012] According to a preferred embodiment of the present invention, the preparation steps of the biochar demulsifier include: A1. Under nitrogen protection, add 9.5-10.5 parts by weight of ferric chloride hexahydrate and 5.1-5.5 parts by weight of ferrous sulfate heptahydrate to a reactor, add 180-220 parts by weight of deionized water, and stir at 25-60°C; then add ammonia water to adjust the pH to 9.5-10.5; then add 1.0-2.0 parts by weight of sodium citrate, and continue the reaction to obtain a mixture; magnetically separate the mixture to obtain a precipitate; wash the precipitate successively with deionized water and anhydrous ethanol, and vacuum dry to obtain citrate-stabilized magnetite nanonuclei. A2. Place 5.0-8.0 parts of citrate-stabilized magnetite nanonuclei in a reactor, add 160-200 parts of anhydrous ethanol, 20-25 parts of deionized water and 3.0-5.0 parts of ammonia water, and disperse by ultrasonication; then add 6.0-9.0 parts of tetraethyl orthosilicate dropwise, and stir the reaction at 25-35℃ to obtain the reaction product; magnetically separate the reaction product to obtain the precipitate; wash the precipitate successively with anhydrous ethanol and deionized water, and vacuum dry to obtain a silica-coated magnetite magnetic framework; A3. Add 6.0-9.0 parts of silica-coated iron(III) oxide magnetic framework to a reaction vessel, along with 180-240 parts of deionized water, 2.0-4.0 parts of lanthanum nitrate hexahydrate, 1.5-3.0 parts of cerium nitrate hexahydrate, 1.0-2.0 parts of zirconium oxychloride octahydrate, 1.0-2.0 parts of ferric nitrate nonahydrate, 6.0-10.0 parts of urea, and 0.5-1.0 parts of polyvinylpyrrolidone. Disperse the mixture ultrasonically. Seal the reaction vessel and place it in an oven. Heat the mixture to 140-160℃ and react. Then, allow it to cool naturally to room temperature to obtain reaction product A. Magneticly separate reaction product A to obtain a precipitate. Wash the precipitate sequentially with deionized water and anhydrous ethanol, and vacuum dry to obtain lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework. A4. Add 6.0-8.0 parts of lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework to a reactor, add 120-160 parts of deionized water and 1.5-2.5 parts of sodium metasilicate, and stir to disperse. Then add 0.8-1.5 parts of ammonium dihydrogen phosphate, and stir to react at 35-45℃ to obtain reaction product B. Magneticly separate reaction product B to obtain a solid product. Wash the solid product with deionized water and vacuum dry to obtain a dried solid product. Place the dried solid product in a tube furnace, heat to 300-500℃ under a nitrogen atmosphere, cool naturally to room temperature, grind and sieve to obtain magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles. Add 80-100 parts of biochar, 12-20 parts of magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles, 300-450 parts of deionized water and 80-120 parts of anhydrous ethanol to a reactor, stir to react, filter, wash, and dry.

[0013] In this invention, the preparation mechanism of the biochar demulsifier involves dissolving ferric chloride hexahydrate and ferrous sulfate heptahydrate in deionized water under nitrogen protection to form a homogeneous iron salt system containing ferric and ferrous ions. After adding ammonia and adjusting to alkalinity, the ferric and ferrous ions hydrolyze simultaneously and co-precipitate, forming a magnetite precipitate. Subsequently, sodium citrate is added, and the citrate ions coordinate with the iron sites on the surface of the magnetite precipitate particles, resulting in a hydrophilic coordination layer on the particle surface, reducing the tendency for aggregation between magnetic particles. After magnetic separation, washing, and vacuum drying, citrate-stabilized magnetite magnetic nanonuclei are obtained. When the citrate-stabilized magnetite magnetic nanonuclei enter a dispersion system composed of anhydrous ethanol, deionized water, and ammonia, tetraethyl orthosilicate hydrolyzes in the alkaline alcohol-water environment to generate silanol groups. These silanol groups nucleate, condense, and form a coating layer on the surface of the citrate-stabilized magnetite magnetic nanonuclei, resulting in a silica-coated magnetite magnetic framework. After a silica-coated magnetite (Fe3O4) magnetic framework is introduced into a hydrothermal system consisting of lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, zirconium oxychloride octahydrate, ferric nitrate nonahydrate, urea, and polyvinylpyrrolidone (PVP), the urea gradually decomposes and releases alkaline components during heating. This causes the lanthanum, cerium, zirconium, and iron components to gradually hydrolyze, deposit, and adhere to the surface of the silica-coated magnetite magnetic framework. PVP inhibits disordered particle aggregation and participates in the dispersion regulation of the lamellar structure, thereby obtaining lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework. Subsequently, sodium metasilicate provides silicate ions in deionized water. The silicate ions adsorb, coordinate, and deposit with the hydroxyl groups and metal sites on the surface of the lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with the magnetic framework. After the addition of ammonium dihydrogen phosphate, the phosphate ions further participate in surface complexation and bridging, allowing the phosphorus-silicon components to be distributed on the surface of the lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with the magnetic framework. After magnetic separation, washing, vacuum drying, and nitrogen atmosphere heat treatment, the hydrated and basic components in the composite precursor undergo dehydration and solidification to form magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles. When these magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles are mixed with commercially available biochar in a deionized water and anhydrous ethanol system, they are co-loaded onto the surface and pores of the commercially available biochar through adsorption in the biochar channels, surface hydroxyl interactions, electrostatic interactions, and particle embedding. After stirring, filtration, washing, and drying, a biochar demulsifier is obtained.

[0014] According to a preferred embodiment of the present invention, in step A1, the stirring time at 25-60°C is 20-40 min.

[0015] According to a preferred embodiment of the present invention, in step A2, the stirring reaction time at 25-35°C is 5-7 hours.

[0016] According to a preferred embodiment of the present invention, in step A3, the reaction time at 140-160°C is 8-12 hours.

[0017] According to a preferred embodiment of the present invention, in step A4, the stirring reaction time at 35-45°C is 2-3 hours, and the treatment time at 300-500°C is 2-3 hours.

[0018] The beneficial effects of this invention are as follows: This invention utilizes biochar as a demulsifier to treat oilfield produced fluids, thereby improving the destabilization efficiency of emulsified oil droplets and the rate of oil-water stratification. The biochar demulsifier contains biochar and magnetic lanthanum, cerium, zirconium, iron, phosphorus, and silicon nanoparticles. Biochar possesses porous adsorption and surface enrichment properties, enabling it to adsorb dispersed oil droplets, colloids, asphaltenes, and suspended particles in the oilfield produced fluid. The magnetic lanthanum, cerium, zirconium, iron, phosphorus, and silicon nanoparticles enhance the contact between the biochar demulsifier and the oil-water interface film, reducing the interfacial film strength and promoting collision, deformation, and aggregation of fine oil droplets. This results in a more easily stratified aggregated system, improving the separation clarity of the oil layer, water layer, and demulsifier-containing solid enrichment layer in the three-phase system.

[0019] The biochar demulsifier of this invention is constructed stepwise from citrate-stabilized magnetite nanocores, silica-coated magnetite magnetic frameworks, lanthanum-cerium-zirconium-iron composite precursor nanoparticles coating the magnetic framework, and magnetic lanthanum-cerium-zirconium-iron-phosphorus silicon nanoparticles. The citrate-stabilized magnetite nanocores endow the material with magnetic responsiveness, while the silica-coated magnetite magnetic framework improves the stability and dispersibility of the magnetic components. The structure formed by the lanthanum-cerium-zirconium-iron composite precursor nanoparticles coating the magnetic framework after treatment with sodium metasilicate and ammonium dihydrogen phosphate enhances the biochar demulsifier's interfacial adsorption, particle bridging, and oil droplet coalescence capabilities, resulting in better demulsification efficiency and easier recycling compared to ordinary biochar.

[0020] The oil-water separation method of this invention combines filtration, heating and stirring, external magnetic field enrichment, and stratified collection. The process is simple and suitable for the synergistic separation of emulsified oil, suspended particles, and biochar demulsifier in oilfield produced fluids. An external magnetic field is placed at the bottom of the oil-water separator, which promotes the accumulation of biochar demulsifier containing magnetic lanthanum, cerium, zirconium, iron, phosphorus, and silicon nanoparticles at the bottom. This facilitates the collection of the demulsifier-containing solid enrichment layer from the bottom of the three-phase system. After elution with anhydrous ethanol, washing, and drying, the surface oil residue of the demulsifier-containing solid enrichment layer is reduced, maintaining good reusability of the biochar demulsifier and thus reducing demulsifier loss and processing costs. Attached Figure Description

[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. The drawings are only used to illustrate the implementation methods and are not intended to limit the present invention.

[0022] Figure 1SEM image of the magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles prepared in Example 1.

[0023] Figure 2 The image shows the XRD pattern of the magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles prepared in Example 1. Detailed Implementation

[0024] The following detailed embodiments are only used to further illustrate this application and should not be construed as limiting the scope of protection of this application. Those skilled in the art can make some non-essential improvements and adjustments to this application based on the above application content.

[0025] Example 1 This embodiment provides a method for oil-water separation using biochar as a demulsifier to treat oilfield produced fluids, the steps of which include: S1. 1000g of oilfield produced fluid was filtered through a filter cloth and added to a demulsification reactor. The oilfield produced fluid was stirred evenly at 25℃ before treatment and sampled and used immediately. The oilfield produced fluid was heated to 50℃ and stirred at 300r / min for 7.5min to obtain pretreated oilfield produced fluid. 1.75g ​​of biochar demulsifier was added to the pretreated oilfield produced fluid and stirred at 300r / min for 5min to obtain a demulsifier dispersion system.

[0026] S2. Transfer the demulsifier dispersion system to an oil-water separator and stir at 200 r / min for 4.5 min at 50°C to obtain the agglomeration system.

[0027] S3. Let the agglomeration system stand for 30 minutes, and apply an external magnetic field to the bottom of the oil-water separator. The magnetic field strength of the external magnetic field is 200mT. The external magnetic field is applied for 30 minutes to obtain a three-phase system.

[0028] S4. Collect the oil layer from the upper part of the three-phase system, discharge the water layer from the middle part of the three-phase system and filter it through a filter membrane to obtain treated water; collect the solid enrichment layer containing demulsifier from the bottom of the three-phase system, add the solid enrichment layer containing demulsifier to 100g of anhydrous ethanol and stir and wash for 10min, filter and collect the solid; wash the washed solid with 100g of deionized water twice, and then dry it at 70℃ for 8h to obtain the dried regenerated biochar demulsifier.

[0029] Preparation steps of biochar demulsifier: A1. Nitrogen gas is introduced into a glass reactor equipped with a mechanical stirrer, thermometer, nitrogen inlet tube, and pH meter for 15 minutes to replace the air in the reactor. The nitrogen flow rate is controlled at 100 mL / min. Under nitrogen protection, 10.0 g of ferric chloride hexahydrate and 5.3 g of ferrous sulfate heptahydrate are added to the reactor, along with 200 g of deionized water. The mixture is stirred at 300 r / min for 30 minutes at 42.5 °C to completely dissolve the ferric chloride hexahydrate and ferrous sulfate heptahydrate, obtaining an iron salt solution. Subsequently, under continuous nitrogen protection and stirring at 300 r / min, ammonia solution with an ammonia content of 25% is added dropwise until the pH of the system reaches 1. During the dropwise addition, the system temperature was controlled at 42.5℃. After the dropwise addition was completed, stirring was continued for 5 minutes. Then, 1.5g of sodium citrate was added, and the reaction was continued for 75 minutes to obtain a mixture. The mixture was placed in a magnetic field for magnetic separation for 10 minutes, and the supernatant was discarded to obtain a precipitate. The precipitate was dispersed in 100g of deionized water and then magnetically separated. The washing was repeated 3 times. The precipitate was then dispersed in 80g of anhydrous ethanol and magnetically separated. The washing was repeated 2 times. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60℃ and a vacuum degree of -0.08MPa for 8 hours to obtain citrate-stabilized iron(III) oxide magnetic nanonuclei.

[0030] A2. Place 6.5g of citrate-stabilized magnetite nanonuclei in a glass reactor equipped with a mechanical stirrer and a thermometer. Add 180g of anhydrous ethanol, 22.5g of deionized water, and 4.0g of ammonia solution (ammonia content 25%). Disperse the mixture ultrasonically for 25min at a power of 300W, controlling the system temperature to not exceed 30℃ during the ultrasonication process. After ultrasonication, stir at 400r / min at 30℃, and then add 7.5g of tetraethyl orthosilicate dropwise to the reactor over a period of 30min. After the addition was completed, the mixture was stirred at 30°C for 6 hours to obtain the reaction product. The reaction product was placed in a magnetic field for 10 minutes for magnetic separation, and the supernatant was discarded to obtain the precipitate. The precipitate was dispersed in 80g of anhydrous ethanol and then magnetically separated. The washing was repeated 3 times. The precipitate was then dispersed in 80g of deionized water and magnetically separated. The washing was repeated 3 times. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60°C and a vacuum degree of -0.08MPa for 8 hours to obtain a silica-coated iron oxide magnetic framework.

[0031] A3. Add 7.5g of silica-coated iron(III) oxide magnetic framework to a polytetrafluoroethylene-lined reactor. Add 210g of deionized water, 3.0g of lanthanum nitrate hexahydrate, 2.25g of cerium nitrate hexahydrate, 1.5g of zirconium oxychloride octahydrate, 1.5g of ferric nitrate nonahydrate, 8.0g of urea, and 0.75g of polyvinylpyrrolidone. Disperse the mixture ultrasonically for 25 minutes at a power of 300W, ensuring the system temperature does not exceed 30℃ during the ultrasonic process. After ultrasonication, seal the reactor and place it in an oven at 150℃ for 1 minute. After 0 h, the mixture was naturally cooled to room temperature to obtain reaction product A. The reaction product A was transferred to a beaker and placed in a magnetic field for magnetic separation for 10 min. The supernatant was discarded to obtain a precipitate. The precipitate was dispersed in 100 g of deionized water and then magnetically separated. The washing was repeated 3 times. The precipitate was then dispersed in 80 g of anhydrous ethanol and magnetically separated. The washing was repeated 2 times. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60 °C and a vacuum degree of -0.08 MPa for 8 h to obtain a magnetic framework coated with lanthanum-cerium-zirconium-iron composite precursor nanoparticles.

[0032] A4. 7.0 g of lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework were added to a glass reactor, along with 140 g of deionized water and 2.0 g of sodium metasilicate. The mixture was stirred and dispersed at 400 r / min for 30 min at 25 °C. Subsequently, 1.15 g of ammonium dihydrogen phosphate was added, the temperature was raised to 40 °C, and the mixture was stirred and reacted at 400 r / min for 2.5 h at 40 °C to obtain reaction product B. Reaction product B was placed in a magnetic field for magnetic separation for 10 min, and the supernatant was discarded to obtain a solid product. The solid product was dispersed in 100 g of deionized water and then magnetically separated, and washed three times. The washed solid product was placed in a vacuum drying oven and vacuum dried at 60 °C and a vacuum degree of -0.08 MPa for 8 h to obtain a dried product. The dried solid product was placed in a tube furnace and heated to 400℃ for 2.5 h under a nitrogen atmosphere with a nitrogen flow rate of 100 mL / min. After treatment, it was naturally cooled to room temperature under a nitrogen atmosphere, ground, and passed through a 200-mesh sieve to obtain magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles. 90 g of biochar, 16 g of magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles, 375 g of deionized water, and 100 g of anhydrous ethanol were added to a reactor and stirred at 400 r / min for 4 h at 25℃. The mixture was then filtered to obtain a filter cake. The filter cake was washed three times with 150 g of deionized water and then twice with 100 g of anhydrous ethanol. The washed filter cake was placed in a drying oven and dried at 70℃ for 8 h to obtain a biochar demulsifier.

[0033] Figure 1The image shows SEM images of magnetic lanthanum, cerium, zirconium, iron, phosphorus, and silicon nanoparticles. The characteristics presented in the images are highly consistent with the target product: First, the high density of nanoscale particle protrusions on the surface indicates that the multi-metal precursors (hydroxides / oxides of La, Ce, Zr, and Fe) have been successfully loaded onto the surface of the magnetic framework, and no smooth, unloaded bare Fe3O4@SiO2 spheres are observed; Second, the cluster structure is intact without obvious fragmentation or collapse, indicating that the calcination treatment at 300-500℃ did not damage the composite structure; Third, there is natural stacking rather than fusion between the particles, which is consistent with the typical morphology of nanomaterials obtained by urea hydrolysis precipitation and low-temperature calcination; Fourth, this rough hierarchical porous structure can provide a large specific surface area and abundant active sites, which is beneficial for it to play an adsorption and charge neutralization role as a demulsifier at the oil-water interface. In summary, the cauliflower-like hierarchical cluster morphology, uniform distribution of nanoprotrusions, and structural integrity shown in the SEM images all confirm that composite nanoparticles with Fe3O4@SiO2 as the magnetic core and lanthanum, cerium, zirconium, iron, phosphorus, and silicon multi-element active components loaded on the surface were successfully prepared according to steps A1-A4. These nanoparticles can be used as active components in highly efficient magnetic biochar demulsifiers.

[0034] Figure 2The XRD pattern of the magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles is shown. From the provided XRD pattern, the original data (red line) and the pattern after background subtraction (blue line) of the sample show a high degree of consistency in the positions of the characteristic diffraction peaks. Furthermore, they perfectly match the characteristic d values ​​(0.30, 0.25, 0.21, 0.17, 0.16, 0.15 nm) of the standard card below. This confirms the successful synthesis of the target product in the following ways: 1. The presence of the Fe3O4 magnetic core: The strongest diffraction peak in the pattern corresponds to d≈0.25 nm (approximately 2θ=35.5°), and a series of diffraction peaks at d≈0.30, 0.21, 0.17, 0.16, and 0.15 nm correspond to the (220), (311), (400), (422), (511), and (440) crystal planes of the Fe3O4 inverse spinel structure, respectively. 1. Sharp peaks and significant intensity indicate that the magnetite nanonuclei prepared in step A1 have good crystallinity, providing a clear magnetic response basis for the entire composite material. 2. Confirmation of the SiO2 coating layer: A broad and diffuse peak is observed in the 2θ=20-25° range, which is a typical characteristic of amorphous silica, confirming that the tetraethyl orthosilicate hydrolysis products in step A2 have been successfully coated on the surface of the magnetic nuclei, forming an amorphous SiO2 intermediate layer. 3. Loading of lanthanum, cerium, zirconium, iron, phosphorus, and silicon active components: The baseline of the spectrum fluctuates slightly in the low-angle region, and no strong characteristic peaks of La, Ce, Zr, Fe oxides or phosphates are observed, indicating that the multi-metal components and phosphorus and silicon species introduced in steps A3 and A4 are uniformly loaded on the surface of the magnetic framework with high dispersion, low crystallinity, or amorphous morphology, without forming independent crystalline phase aggregations. This is consistent with the surface nanoprotrusion structure observed by SEM, reflecting that the active components are highly dispersed at the nanoscale. Conclusion: XRD results confirmed that the sample consisted of a well-crystallized Fe3O4 magnetic core, an amorphous SiO2 intermediate layer, and a highly dispersed lanthanum-cerium-zirconium-iron-phosphorus-silicon active layer, and the target magnetic composite nanoparticles were successfully synthesized.

[0035] Example 2 The specific implementation method is the same as in Example 1, except that this example provides a method for oil-water separation using biochar as a demulsifier to treat oilfield produced fluids, the steps of which include: S1. After filtering 900g of oilfield produced fluid, add it to the demulsification reactor, heat it to 40℃ and stir for 5min to obtain pretreated oilfield produced fluid; add 0.5g of biochar demulsifier to the pretreated oilfield produced fluid and continue stirring for 5min to obtain demulsifier dispersion system. S2. Transfer the demulsifier dispersion system to an oil-water separator and stir at 40°C for 3 minutes to obtain the agglomeration system; S3. Let the agglomeration system stand for 20 minutes, and apply an external magnetic field to the bottom of the oil-water separator. The magnetic field strength of the external magnetic field is 100mT to obtain a three-phase system. S4. Collect the oil layer from the upper part of the three-phase system, discharge the water layer from the middle part of the three-phase system and filter it to obtain treated water; collect the solid enrichment layer containing demulsifier from the bottom of the three-phase system, elute the solid enrichment layer containing demulsifier with anhydrous ethanol, and use 80g of anhydrous ethanol for elution; wash the eluted solid enrichment layer containing demulsifier with deionized water twice, using 80g of deionized water each time, and then dry it at 70℃ for 8h.

[0036] Preparation steps of biochar demulsifier: A1. Under nitrogen protection, 9.5 g of ferric chloride hexahydrate and 5.1 g of ferrous sulfate heptahydrate were added to a reactor, along with 180 g of deionized water. The mixture was stirred at 25 °C for 20 min. Ammonia was then added to adjust the pH to 9.5. 1.0 g of sodium citrate was then added, and the reaction continued for 60 min to obtain a mixture. The mixture was magnetically separated to obtain a precipitate. The precipitate was washed three times with 90 g of deionized water each time, and then washed twice with 70 g of anhydrous ethanol each time. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain citrate-stabilized magnetite nanonuclei. A2. 5.0 g of citrate-stabilized magnetite nanonuclei were placed in a reactor, and 160 g of anhydrous ethanol, 20 g of deionized water and 3.0 g of ammonia were added. The mixture was ultrasonically dispersed for 25 min. Then, 6.0 g of tetraethyl orthosilicate was added dropwise. After the addition was completed, the mixture was stirred at 25 °C for 5 h to obtain the reaction product. The reaction product was magnetically separated to obtain the precipitate. The precipitate was washed three times with anhydrous ethanol, each time using 70 g of anhydrous ethanol, and then washed three times with deionized water, each time using 70 g of deionized water. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain a silica-coated magnetite framework. A3. 6.0 g of silica-coated iron(III) oxide magnetic framework was added to a reaction vessel, along with 180 g of deionized water, 2.0 g of lanthanum nitrate hexahydrate, 1.5 g of cerium nitrate hexahydrate, 1.0 g of zirconium oxychloride octahydrate, 1.0 g of ferric nitrate nonahydrate, 6.0 g of urea, and 0.5 g of polyvinylpyrrolidone. The mixture was ultrasonically dispersed for 25 min. The reaction vessel was then sealed and placed in an oven, heated to 140 °C, and reacted for 8 h. The mixture was then naturally cooled to room temperature to obtain reaction product A. Reaction product A was magnetically separated to obtain a precipitate. The precipitate was washed three times with 90 g of deionized water each time, and then washed twice with 70 g of anhydrous ethanol each time. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework. A4. 6.0 g of lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework were added to a reactor, along with 120 g of deionized water and 1.5 g of sodium metasilicate. The mixture was stirred and dispersed for 30 min. Subsequently, 0.8 g of ammonium dihydrogen phosphate was added, and the mixture was stirred and reacted at 35 °C for 2 h to obtain reaction product B. Reaction product B was magnetically separated to obtain a solid product. The solid product was washed three times with 90 g of deionized water each time. The washed solid product was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain a dried solid product. The dried solid product was then placed in a tube... In a nitrogen atmosphere, the temperature was raised to 300℃ for 2 hours in a furnace, and then naturally cooled to room temperature. The nanoparticles were then ground and sieved to obtain magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles. 80g of biochar, 12g of magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles, 300g of deionized water and 80g of anhydrous ethanol were added to a reactor and stirred for 4 hours. The mixture was then filtered to obtain a filter cake. The filter cake was washed three times with 120g of deionized water each time, and then washed twice with 80g of anhydrous ethanol each time. The washed filter cake was placed in a drying oven and dried at 70℃ for 8 hours to obtain a biochar demulsifier.

[0037] Example 3 The specific implementation method is the same as in Example 1, except that this example provides a method for oil-water separation using biochar as a demulsifier to treat oilfield produced fluids, the steps of which include: S1. Filter 1100g of oilfield produced fluid and add it to the demulsification reactor. Heat the mixture to 60℃ and stir for 10min to obtain pretreated oilfield produced fluid. Add 3.0g of biochar demulsifier to the pretreated oilfield produced fluid and continue stirring for 5min to obtain the demulsifier dispersion system. S2. Transfer the demulsifier dispersion system to an oil-water separator and stir at 60°C for 6 minutes to obtain the agglomeration system; S3. Let the agglomeration system stand for 40 minutes, and apply an external magnetic field to the bottom of the oil-water separator. The magnetic field strength of the external magnetic field is 300mT to obtain a three-phase system. S4. Collect the oil layer from the upper part of the three-phase system, discharge the water layer from the middle part of the three-phase system and filter it to obtain treated water; collect the solid enrichment layer containing demulsifier from the bottom of the three-phase system, elute the solid enrichment layer containing demulsifier with anhydrous ethanol, the amount of anhydrous ethanol used for elution is 120g; wash the eluted solid enrichment layer containing demulsifier with deionized water twice, the amount of deionized water used each time is 120g, and then dry it at 70℃ for 8h.

[0038] Preparation steps of biochar demulsifier: A1. Under nitrogen protection, 10.5 g of ferric chloride hexahydrate and 5.5 g of ferrous sulfate heptahydrate were added to a reactor, along with 220 g of deionized water. The mixture was stirred at 60 °C for 40 min. Ammonia was then added to adjust the pH to 10.5. 2.0 g of sodium citrate was then added, and the reaction continued for 90 min to obtain a mixture. The mixture was magnetically separated to obtain a precipitate. The precipitate was washed three times with 110 g of deionized water each time, and then washed twice with 90 g of anhydrous ethanol each time. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain citrate-stabilized magnetite nanonuclei. A2. 8.0 g of citrate-stabilized magnetite nanonuclei were placed in a reactor, and 200 g of anhydrous ethanol, 25 g of deionized water and 5.0 g of ammonia were added. The mixture was ultrasonically dispersed for 25 min. Then, 9.0 g of tetraethyl orthosilicate was added dropwise. After the addition was completed, the mixture was stirred at 35 °C for 7 h to obtain the reaction product. The reaction product was magnetically separated to obtain a precipitate. The precipitate was washed three times with anhydrous ethanol, each time using 90 g of anhydrous ethanol, and then washed three times with deionized water, each time using 90 g of deionized water. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain a silica-coated magnetite magnetic framework. A3. 9.0 g of silica-coated iron(III) oxide magnetic framework was added to a reaction vessel, along with 240 g of deionized water, 4.0 g of lanthanum nitrate hexahydrate, 3.0 g of cerium nitrate hexahydrate, 2.0 g of zirconium oxychloride octahydrate, 2.0 g of ferric nitrate nonahydrate, 10.0 g of urea, and 1.0 g of polyvinylpyrrolidone. The mixture was ultrasonically dispersed for 25 min. The reaction vessel was then sealed and placed in an oven, heated to 160 °C, and reacted for 12 h. The mixture was then naturally cooled to room temperature to obtain reaction product A. Reaction product A was magnetically separated to obtain a precipitate. The precipitate was washed three times with 110 g of deionized water each time, and then washed twice with 90 g of anhydrous ethanol each time. The washed precipitate was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework. A4. 8.0 g of lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework were added to a reactor, along with 160 g of deionized water and 2.5 g of sodium metasilicate. The mixture was stirred and dispersed for 30 min. Subsequently, 1.5 g of ammonium dihydrogen phosphate was added, and the mixture was stirred and reacted at 45 °C for 3 h to obtain reaction product B. Reaction product B was magnetically separated to obtain a solid product. The solid product was washed three times with deionized water, using 110 g of deionized water each time. The washed solid product was placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain a dried solid product. The dried solid product was then placed in a tubular... In a furnace, under a nitrogen atmosphere, the temperature was raised to 500℃ for 3 hours, and then naturally cooled to room temperature. The nanoparticles were then ground and sieved to obtain magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles. 100g of biochar, 20g of magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles, 450g of deionized water and 120g of anhydrous ethanol were added to a reactor and stirred for 4 hours. The mixture was then filtered to obtain a filter cake. The filter cake was washed three times with 180g of deionized water each time, and then washed twice with 120g of anhydrous ethanol each time. The washed filter cake was placed in a drying oven and dried at 70℃ for 8 hours to obtain a biochar demulsifier.

[0039] Comparative Example 1 The specific implementation method is the same as in Example 1, except that an equal mass of biochar is used to replace the biochar demulsifier in the treatment of the oilfield produced fluid, and the rest is the same as in Example 1.

[0040] Comparative Example 2 The specific implementation method is the same as in Example 1, except that the demulsifier prepared by mixing the citrate-stabilized iron oxide magnetic nanonucleus obtained in step A1 of Example 1 with biochar is used instead of an equal mass of biochar demulsifier. The rest is the same as in Example 1.

[0041] Comparative Example 3 The specific implementation method is the same as in Example 1, except that the demulsifier prepared by mixing the silica-coated iron oxide magnetic framework obtained in steps A1 and A2 of Example 1 with biochar is used instead of an equal mass of biochar demulsifier. The rest is the same as in Example 1.

[0042] Performance testing The oil-water separation methods for treating oilfield produced fluids using biochar demulsifiers provided in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing according to the following steps: The biochar demulsifier and comparative demulsifier prepared in Examples 1-3 and Comparative Examples 1-3 were used as test samples. The same batch of oilfield produced fluid was used as the test object. Before the test, the oilfield produced fluid was placed in a sealed container and stirred at 25°C for 10 minutes to redisperse the oil droplets and suspended particles in the oilfield produced fluid evenly. 1000g of oilfield produced fluid was weighed and added to the demulsification reactor. Biochar demulsifier or comparative demulsifier was added according to the process conditions recorded in the corresponding examples or comparative examples, and oil-water separation treatment was completed. After the treatment, a sample was taken from the middle water layer of the three-phase system. The sampling location avoided the upper oil layer and the bottom solid enrichment layer containing demulsifier. The sampling volume was 100mL. After sampling, the treated water sample was obtained by filtration through a filter membrane.

[0043] The method for testing the oil content in treated water is as follows: 50 mL of treated water sample is added to a separatory funnel, 50 mL of petroleum ether is added, the mixture is shaken and extracted for 3 min, and after standing for 10 min, the organic phase is separated. The extraction is repeated once, and the two organic phases are combined and diluted to 100 mL. The absorbance is measured at a set wavelength using a spectrophotometer. The oil content in the treated water is calculated based on the pre-established crude oil standard curve, and the unit is mg / L.

[0044] The method for testing the oil removal rate is as follows: the initial oil content of the oilfield produced fluid before treatment is determined according to the same extraction and determination method, and the oil removal rate is calculated according to "the difference between the initial oil content of the oilfield produced fluid before treatment and the oil content of the treated water ÷ the initial oil content of the oilfield produced fluid before treatment × 100%", with the unit being 100%.

[0045] The test method for turbidity removal rate is as follows: Take 30 mL of each of the oilfield produced fluid before treatment and the treated water sample, place them in the sample cell of the turbidity meter, gently invert and mix them 3 times before testing to avoid introducing air bubbles, read the turbidity value, and calculate according to "turbidity removal rate = difference between turbidity of oilfield produced fluid before treatment and turbidity of treated water ÷ turbidity of oilfield produced fluid before treatment × 100%", with the unit being .

[0046] The test method for chemical oxygen demand (COD) removal rate is as follows: Take 10 mL of each of the oilfield produced fluid before treatment and the treated water sample, add them to a digestion tube, add oxidative digestion reagent, digest at 150℃ for 120 min, cool to room temperature, and determine the COD by spectrophotometry. The COD removal rate is calculated as follows: "COD removal rate = difference between COD of oilfield produced fluid before treatment and COD of treated water ÷ COD of oilfield produced fluid before treatment × 100%", with units of 100%.

[0047] The test method for three-phase separation time is as follows: time is started when biochar demulsifier or comparative demulsifier is added to the oilfield produced fluid and stirring begins. After stirring, settling and enrichment by an external magnetic field, the interface changes of the upper oil layer, the middle water layer and the bottom demulsifier-containing solid enrichment layer in the system are observed. When the interface between the oil layer and the water layer is clear, the bottom demulsifier-containing solid enrichment layer no longer diffuses significantly and the interface position does not change significantly within 5 minutes, the time is stopped and the time is recorded in minutes.

[0048] The test method for demulsifier recovery rate is as follows: Record the initial mass of biochar demulsifier or control demulsifier added in each test group. After the treatment, collect the solid enrichment layer containing demulsifier from the bottom of the three-phase system, elute with 100 mL of anhydrous ethanol for 10 min, wash twice with 100 mL of deionized water, dry at 70 °C for 8 h, cool to room temperature, and weigh the recovered solid mass. Calculate the recovery rate according to "demulsifier recovery rate = recovered solid mass ÷ initial mass of biochar demulsifier or control demulsifier × 100%", with units of 0.5%.

[0049] The test method for recycling retention rate is as follows: the recovered and dried biochar demulsifier or comparative demulsifier is used to treat the next batch of produced fluid from the same source oilfield at the original dosage, and this is repeated 5 times. The oil removal rate is measured each time using the same method. The recycling retention rate is calculated as "recycling retention rate = oil removal rate of the 5th treatment ÷ oil removal rate of the 1st treatment × 100%", with the unit being %; each test item is tested in parallel 3 times, and the arithmetic mean of the 3 test results is taken as the final result.

[0050] Test results: Table 1: Test results of each embodiment and comparative example ; As can be seen from Table 1, Examples 1-3 show significant advantages over Comparative Examples 1-3 in terms of treated water oil content, oil removal rate, turbidity removal rate, chemical oxygen demand removal rate, three-phase separation time, demulsifier recovery rate, and recycling retention rate. This indicates that the present invention can effectively solve the problems of insufficient demulsification efficiency, slow oil-water separation speed, high oil content in effluent, insufficient pollutant removal, difficulty in demulsifier recovery, and poor recycling stability of existing biochar demulsifiers.

[0051] Specifically, the oil content of the treated water in Examples 1-3 was 18.6 mg / L, 28.4 mg / L, and 14.9 mg / L, respectively, which was significantly lower than that of Comparative Example 1 (126.8 mg / L), Comparative Example 2 (74.5 mg / L), and Comparative Example 3 (46.2 mg / L). This indicates that using biochar alone, mixing biochar with citrate-stabilized magnetite nanocores, or mixing biochar with silica-coated magnetite frameworks, are all insufficient to fully disrupt the interfacial film of stable emulsified oil droplets in oilfield produced fluids. However, Examples 1-3, using biochar as a demulsifier, significantly reduced the residual oil content in the treated water.

[0052] The oil removal rates of Examples 1-3 reached 97.1%, 95.6%, and 97.7%, respectively, which were higher than those of Comparative Example 1 (80.4%), Comparative Example 2 (88.5%), and Comparative Example 3 (92.9%). This indicates that the biochar demulsifier obtained by the stepwise construction of citrate-stabilized magnetite nanonuclei, silica-coated magnetite framework, lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with magnetic framework, and magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles can improve the adsorption, bridging, and aggregation capabilities of biochar demulsifier for emulsified oil droplets.

[0053] The turbidity removal rate of Examples 1-3 was 94.2-97.0%, and the chemical oxygen demand removal rate was 78.9-84.5%, both of which were significantly better than those of Comparative Examples 1-3. This indicates that the present invention can not only remove the oil phase, but also simultaneously enrich and remove suspended particles, colloids, asphaltenes and other organic pollutants, thereby improving the clarity of the treated water and the removal effect of organic pollutants.

[0054] The three-phase separation time of Examples 1-3 was 20.6-31.8 min, which was shorter than that of Comparative Example 1 (47.2 min), Comparative Example 2 (38.6 min), and Comparative Example 3 (30.4 min). This indicates that the introduction of magnetic lanthanum, cerium, zirconium, iron, phosphorus, and silicon nanoparticles can promote the rapid aggregation of fine oil droplets and accelerate the formation of a solid enrichment layer containing demulsifier under the action of an external magnetic field, thereby shortening the separation time of the oil layer, water layer, and solid enrichment layer containing demulsifier.

[0055] The demulsifier recovery rates of Examples 1-3 were 91.8-95.2%, which were significantly higher than 48.3% of Comparative Example 1, and also better than 86.5% of Comparative Example 2 and 90.7% of Comparative Example 3. This indicates that ordinary biochar lacks effective magnetic response and is difficult to recover efficiently. Although introducing a magnetic structure of iron oxide or coating the magnetic framework of iron oxide with silica can improve the recovery performance, it is not as good as the complete magnetic lanthanum, cerium, zirconium, iron, phosphorus and silicon nanoparticle composite structure.

[0056] The recycling retention rate of Examples 1-3 was 87.6-92.1%, higher than that of Comparative Example 1 (41.5%), Comparative Example 2 (75.3%), and Comparative Example 3 (82.6%). This indicates that the biochar demulsifier of the present invention can still maintain good demulsification activity and magnetic field enrichment ability after elution with anhydrous ethanol, washing, and drying, thus reducing demulsifier consumption and operating costs. Therefore, based on the above data, it can be shown that the present invention effectively solves the technical problems of unstable emulsion of oilfield produced fluid, high oil content in the produced water, long separation time, difficulty in recovering demulsifier, and insufficient recycling performance in the prior art compared to Comparative Examples 1-3.

[0057] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for oil-water separation using biochar as a demulsifier to treat oilfield produced fluids, characterized in that, Includes the following steps: S1. By weight, filter 900-1100 parts of oilfield produced fluid and add it to the demulsification reactor. Heat the mixture to 40-60℃ and stir to obtain pretreated oilfield produced fluid. Add 0.5-3.0 parts of biochar demulsifier to the pretreated oilfield produced fluid and continue stirring to obtain a demulsifier dispersion system. S2. Transfer the demulsifier dispersion system to an oil-water separator and stir at 40-60℃ to obtain an agglomeration system; S3. Allow the aggregated system to stand, and apply an external magnetic field to the bottom of the oil-water separator to obtain a three-phase system; S4. Collect the oil layer from the upper part of the three-phase system, discharge the water layer from the middle of the three-phase system and filter it to obtain treated water; The solid enrichment layer containing demulsifier was collected from the bottom of the three-phase system, and the solid enrichment layer containing demulsifier was eluted with anhydrous ethanol, washed and dried. The preparation steps of the biochar demulsifier include: A1. Under nitrogen protection, add 9.5-10.5 parts by weight of ferric chloride hexahydrate and 5.1-5.5 parts by weight of ferrous sulfate heptahydrate to a reactor, add 180-220 parts by weight of deionized water, and stir at 25-60°C; then add ammonia water to adjust the pH to 9.5-10.5; then add 1.0-2.0 parts by weight of sodium citrate, and continue the reaction to obtain a mixture; magnetically separate the mixture to obtain a precipitate; wash the precipitate successively with deionized water and anhydrous ethanol, and vacuum dry to obtain citrate-stabilized magnetite nanonuclei. A2. Place 5.0-8.0 parts of citrate-stabilized magnetite nanonuclei in a reactor, add 160-200 parts of anhydrous ethanol, 20-25 parts of deionized water and 3.0-5.0 parts of ammonia water, and disperse by ultrasonication; then add 6.0-9.0 parts of tetraethyl orthosilicate dropwise, and stir the reaction at 25-35℃ to obtain the reaction product; magnetically separate the reaction product to obtain the precipitate; wash the precipitate successively with anhydrous ethanol and deionized water, and vacuum dry to obtain a silica-coated magnetite magnetic framework; A3. Add 6.0-9.0 parts of silica-coated iron(III) oxide magnetic framework to a reaction vessel, along with 180-240 parts of deionized water, 2.0-4.0 parts of lanthanum nitrate hexahydrate, 1.5-3.0 parts of cerium nitrate hexahydrate, 1.0-2.0 parts of zirconium oxychloride octahydrate, 1.0-2.0 parts of ferric nitrate nonahydrate, 6.0-10.0 parts of urea, and 0.5-1.0 parts of polyvinylpyrrolidone. Disperse the mixture ultrasonically. Seal the reaction vessel and place it in an oven. Heat the mixture to 140-160℃ and react. Then, allow it to cool naturally to room temperature to obtain reaction product A. Magneticly separate reaction product A to obtain a precipitate. Wash the precipitate sequentially with deionized water and anhydrous ethanol, and vacuum dry to obtain lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework. A4. Add 6.0-8.0 parts of lanthanum-cerium-zirconium-iron composite precursor nanoparticles coated with a magnetic framework to a reactor, add 120-160 parts of deionized water and 1.5-2.5 parts of sodium metasilicate, and stir to disperse. Then add 0.8-1.5 parts of ammonium dihydrogen phosphate, and stir to react at 35-45℃ to obtain reaction product B. Magneticly separate reaction product B to obtain a solid product. Wash the solid product with deionized water and vacuum dry to obtain a dried solid product. Place the dried solid product in a tube furnace, heat to 300-500℃ under a nitrogen atmosphere, cool naturally to room temperature, grind and sieve to obtain magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles. Add 80-100 parts of biochar, 12-20 parts of magnetic lanthanum-cerium-zirconium-iron-phosphorus-silicon nanoparticles, 300-450 parts of deionized water and 80-120 parts of anhydrous ethanol to a reactor, stir to react, filter, wash, and dry.

2. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluid according to claim 1, characterized in that, In step S1, the stirring time after heating to 40-60℃ is 5-10 minutes.

3. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluid according to claim 1, characterized in that, In step S2, the stirring time at 40-60℃ is 3-6 minutes.

4. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluids according to claim 1, characterized in that, In step S3, the settling time is 20-40 minutes.

5. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluid according to claim 1, characterized in that, In step S3, the magnetic field strength of the applied magnetic field is 100-300mT.

6. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluid according to claim 1, characterized in that, In step A1, the stirring time at 25-60℃ is 20-40 minutes.

7. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluid according to claim 1, characterized in that, In step A2, the reaction is stirred at 25-35℃ for 5-7 hours.

8. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluid according to claim 1, characterized in that, In step A3, the reaction time is 8-12 hours after heating to 140-160℃.

9. The method for oil-water separation using biochar demulsifier to treat oilfield produced fluid according to claim 1, characterized in that, In step A4, the stirring reaction time at 35-45℃ is 2-3 hours, and the treatment time at 300-500℃ is 2-3 hours.

Citation Information

Patent Citations

  • Preparation method for fluorescence visualized magnetic MOFs demulsifier

    CN110157471A

  • Preparation method of amphiphilic ZIF composite material demulsifier

    CN121930675A